1991
DOI: 10.1002/1097-4679(199103)47:2<266::aid-jclp2270470213>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Black/white IQ differences: Does age make the difference?

Abstract: Data are presented on racial differences from the norms of the Kaufman Assessment Battery for Children, the recent renorming of the Wechsler Adult Intelligence Scale‐Revised, the Stanford‐Binet IV, and Raven's Progressive Matrices. The premise of the present article is that, while the one standard deviation IQ difference between Black and White adults has remained constant, IQ differences between Black and White children are declining. These data are discussed in the context of previous studies on possible rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Preschoolers displayed a 10.8 point difference on the Full Scale IQ, a 10.5 difference on the Verbal IQ, and an 8.9 point difference on the Performance IQ (Tuttle, 1966). The IQ gap also was seen in other measures of cognitive ability (Vincent, 1991). Thorndike et al (1986) found a 10-12 point advantage for Caucasian children from the standardization sample of the Stanford Binet Intelligence Scale, Fourth Edition (SB-IV).…”
Section: Racial Differences In Intelligencementioning
confidence: 99%
See 2 more Smart Citations
“…Preschoolers displayed a 10.8 point difference on the Full Scale IQ, a 10.5 difference on the Verbal IQ, and an 8.9 point difference on the Performance IQ (Tuttle, 1966). The IQ gap also was seen in other measures of cognitive ability (Vincent, 1991). Thorndike et al (1986) found a 10-12 point advantage for Caucasian children from the standardization sample of the Stanford Binet Intelligence Scale, Fourth Edition (SB-IV).…”
Section: Racial Differences In Intelligencementioning
confidence: 99%
“…Given the smallest IQ gap seen in a modern test of intelligence, the K-ABC was seen as an appropriate test to use with an ethnically diverse population (Kaufman & Lichtenberger, 2002). Evidence regarding the closure of the IQ gap in recent years has been mixed with some researchers seeing progress (Vincent, 1991) and others indicating no decrease during the 20 th century (McGurk, 1982;Shuey, 1966).…”
Section: Racial Differences In Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, Vincent (1991) presented evidence for a narrowing difference in IQ scores from the 1980s, but it was vulnerable to technical criticism (Jensen, 1998). A stronger case has been made for the vocabulary test administered by the General Social Survey.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in IQ test scores are usually linked to educational opportunity, language proficiency and general socioeconomic level, with differential changes in test scores between cultural groups (Claassen, 1997;Vincent, 1991). Where certain culture groups or other subgroups are disadvantaged, an improvement in the socioeconomic and educational opportunities of the disadvantaged group results in increases in the mean group score which are beyond the normal population increases over time (Van de Vijver, 1997;Vincent, 1991).…”
Section: Dynamic Testingmentioning
confidence: 99%